Accuracy Of Polyvinyl Siloxane Impression Material With Different Inter Implant Angulation - Haider, Yagthan M. (2015)
Questions have been raised about whether the elasticity of the impression material, the inter-implant angulation, and the combination of these factors affect the impression accuracy of the implant impression. Given its favorable properties, Polyvinyl Siloxane (PVS) has been recommended as an impression material for clinical use, and thus selected for this study. The objectives of this study were to determine the modulus of elasticity of two PVS (medium body) impression materials, to compare the combined effects of impression material elasticity and dental implant analog angulation (0°, 5°, 10°, and 15°) on the accuracy of the impression, to compare the effect of impression material elasticity on the accuracy of the dental implant analog impression regardless of the inter-implant angulation and to compare the effect of dental implant analog angulation regardless of the material elasticity on the accuracy of the impression.